Experimental and numerical study of ultra-short laser-produced collimated Cu Kα X-ray source. (3rd July 2017) - Rathore, R.; Arora, V.; Singhal, H.; Mandal, T.; Chakera, J.A.; Naik, P.A.
Abstract: K α X-ray sources generated from the interaction of ultra-short laser pulses with solids are compact and low-cost source of ultra-short quasi-monochromatic X-rays compared with synchrotron radiation source. Development of collimated ultra-short K α X-ray source by the interaction of 45 fs Ti:sapphire laser pulse with Cu wire target is presented in this paper. A study of the K α source with laser parameters such as energy and pulse duration was carried out. The observed K α X-ray photon flux was ~2.7 × 10 8 photons/shot at the laser intensity of ~2.8 × 10 17 W cm −2 . A model was developed to analyze the observed results. The K α radiation was coupled to a polycapillary collimator to generate a collimated low divergence (0.8 mrad) X-ray beam. Such sources are useful for time-resolved X-ray diffraction and imaging studies.